Breast discomfort after augmentation mammoplasty: a case report - Giancarlo Cervo Rechia; Verônica Hamann Aita (Revista Brasileira de Cirurgia Plástica)
Mammoplasty with prostheses is one of the most performed plastic surgeries in the world. However, the healing process around the implant and the presence of a biofilm can lead to the development of pathologies such as capsular contracture and seroma. These pathologies seem to be physiologically related to the development of lymphoma associated with breast implants (BIA-ALCL), which is also a differential diagnosis. The purpose of this study is to report the case of a patient with breast discomfort who, after two previous surgeries for seroma drainage and prosthesis replacement, presented breast discomfort and alteration in imaging of the left breast. She was, submitted to a capsulectomy in a block of the left breast and complete on the right, having her prostheses replaced. Bia-ALCL investigation tests were negative and pathological findings were suggestive of left capsular contracture and double capsule formation on the right. The study emphasizes the importance of differential diagnosis in mammary pathologies, long-term follow-up, and prophylaxis measures in biofilm formation.